Report on the workshop VET research in Europe : topics, structures and cooperation ; European Vocational Skills Week 2020, Berlin, Germany - Grollmann, Philipp [Herausgeber]; Nägele, Christof [Herausgeber] (My University, 2021)
"This report documents the course and results of an event jointly organised by VETNET and BIBB in cooperation with the European Commission DG Employment, Social Affairs and Inclusion. The event “VET research in Europe: topics, structures and cooperation” was organised on Wednesday, 11th 2020, as part of the European Vocational Skills Week in Berlin, Germany. Because of the COVID-19 pandemic, it was carried out online. It was up to the participants to submit their contributions in written form or only as an overview of their presentation, e.g., as presentation. Workshop facilitators were asked to summarise the discussion in their workshops. In the first and second part, four contributions provide a stimulating input on relevant topics in and structures of VET research in different European countries. Based on the introduction and impetus presentations, the question on how to improve cooperation within the research community and between research and policy was discussed in 11 small groups and is documented by the moderators. At the end of the publications there are conclusions of the organisers on focal points of further developments and cooperation." (Author's abstract ; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; T 1 Forschungsrichtungen; I 2.2 Europa; I 1 Internationale Berufsbildung; 370; Berufsbildung; Berufsbildungsforschung; Europa; Internationale Zusammenarbeit; Bildungseinrichtung; Literaturanalyse; Digitalisierung; Digitalisierung; Berufsschullehrer; Migration; Kernqualifikation